Study of Fault Diagnosis Method for Wind Turbine with Decision Classification Algorithms and Expert System - Feng Yongxin (Institute of Advanced Engineering and Science, 2012)
Study on the fault diagnosis method through the combination of decision classification algorithms and expert system. The method of extracting diagnosis rules with the CTree software was given, and a fault diagnosis system based on CLIPS was developed. In order to verify the feasibility of the method, at first the sample data was got through the simulations under fault of direct-drive wind turbine and gearbox, then the diagnosis rules was extracted with the CTree software, at last the fault diagnosis system proposed and the rules was used to extracted to diagnose the fault simulated. Test results showed that the misdiagnosis rate both within 5%, thus the feasibility of the method was verified. DOI: http://dx.doi.org/10.11591/telkomnika.v10i5.1281